Neonatal pulmonary arteriovenous malformation in hereditary haemorrhagic telangiectasia. Issue 3 (1st November 2002) - Koppen, S; Korver, C R W; Dalinghaus, M; Westermann, C J J
Abstract : A 3 week old infant presented with persistent hypoxaemia and was diagnosed with pulmonary arteriovenous malformations. Her family history was positive for hereditary haemorrhagic telangiectasia. She was treated successfully with coil embolotherapy at the age of 4 months. Transcatheter embolisation may be considered the primary treatment for pulmonary arteriovenous malformations in infancy.